Cisplatin-Induced Hearing Loss, Oxidative Stress, and Antioxidants as a Therapeutic Strategy—A State-of-the-Art Review - Olaf Rose; Tim Croonenberg; Stephanie Clemens; Tobias Hinteregger; Stefanie Eppacher; Petra Huber-Cantonati; Marta Garcia-Miralles; Raffaella Liuni; Silvia Dossena (Antioxidants)
Cisplatin is an established component of treatment protocols for various solid malignancies but carries a significant potential for serious adverse effects. Ototoxicity from cisplatin treatment is an important dose-limiting toxicity that manifests as bilateral, progressive, irreversible, dose-dependent sensorineural hearing loss, ear pain, tinnitus, and vestibular dysfunction. Despite the recent approval of sodium thiosulphate for the prevention of cisplatin-induced hearing loss (CIHL) in pediatric patients, structured prevention programs are not routinely implemented in most hospitals, and reducing platinum-induced ototoxicity in adults remains an important clinical problem without established treatment options. Cochlear oxidative stress plays a fundamental role in CIHL. Here, we review the molecular mechanisms leading to oxidative stress in CIHL and the clinical and preclinical studies testing antioxidants in CIHL to guide future clinical trials in assessing the efficacy and safety of candidate antioxidant compounds in this clinical setting.